Răspuns :
a) 3√2x / 3√2 = 9√14 / 3√2
x = 3√7
b) 2√3x / 2√3 = 6√15 / 2√3
x = 3√5
c) 4√7x / 4√7 = 8√35 / 4√7
x = 2√5
d) -4√5x / -4√5 = 8√10 / -4√5
x = 2√2 / 1
e) 2√2x / 2√2 = -4√14 / 2√2
x = - 2√5
f) -3√3x / -3√3 = 9√22 / -3√3
x = 3√22 / -√3.
x = 3√7
b) 2√3x / 2√3 = 6√15 / 2√3
x = 3√5
c) 4√7x / 4√7 = 8√35 / 4√7
x = 2√5
d) -4√5x / -4√5 = 8√10 / -4√5
x = 2√2 / 1
e) 2√2x / 2√2 = -4√14 / 2√2
x = - 2√5
f) -3√3x / -3√3 = 9√22 / -3√3
x = 3√22 / -√3.
a) 3√2x / 3√2 = 9√14 / 3√2
x = 3√2
b) 2√3x / 2√3 = 6√15 / 2√3
x = 3√5
c) 4√7x / 4√7 = 8√35 / 4√7
x = 2√5
d) -4√5x / -4√5 = 8√10 / -4√5
x = -2√2
e) 2√2x / 2√2 = -4√14 / 2√2
x = - 2√7
f) -3√3x / -3√3 = 9√22 / -3√3
x = 3√22 / -√3= - 3√66/3= - √66
x = 3√2
b) 2√3x / 2√3 = 6√15 / 2√3
x = 3√5
c) 4√7x / 4√7 = 8√35 / 4√7
x = 2√5
d) -4√5x / -4√5 = 8√10 / -4√5
x = -2√2
e) 2√2x / 2√2 = -4√14 / 2√2
x = - 2√7
f) -3√3x / -3√3 = 9√22 / -3√3
x = 3√22 / -√3= - 3√66/3= - √66